2013
DOI: 10.1021/ja309153x
|View full text |Cite
|
Sign up to set email alerts
|

Besting Vitamin E: Sidechain Substitution is Key to the Reactivity of Naphthyridinol Antioxidants in Lipid Bilayers

Abstract: A series of naphthyridinol analogs of α-tocopherol (α-TOH, right) with varying sidechain substitution was synthesized to determine how systematic changes in the lipophilicity of these potent antioxidants impact their radical-trapping activities in lipid bilayers, regenerability by water-soluble reductants, and binding to human tocopherol transport protein (TTP). The activities of the naphthyridinols were assayed in phosphatidylcholine unilamellar liposomes using a recently developed high-throughput assay that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 56 publications
2
65
0
1
Order By: Relevance
“…An example of the former is the application to study novel naphthyridinol antioxidants ( Figure 2A). 101 Here, probe oxidation is completely suppressed by the antioxidant, even at very low loadings, corresponding to k inh values at least 30-fold greater than for α-TOH. An example of the latter is the application of the probe to study the RTA activity of allicin and petviercin, the purported antioxidants in garlic and anamu, respectively.…”
Section: Iii3 Competition With Fluorogenic Substratesmentioning
confidence: 82%
“…An example of the former is the application to study novel naphthyridinol antioxidants ( Figure 2A). 101 Here, probe oxidation is completely suppressed by the antioxidant, even at very low loadings, corresponding to k inh values at least 30-fold greater than for α-TOH. An example of the latter is the application of the probe to study the RTA activity of allicin and petviercin, the purported antioxidants in garlic and anamu, respectively.…”
Section: Iii3 Competition With Fluorogenic Substratesmentioning
confidence: 82%
“…24 The probe, which consists of a BODIPY fluorophore connected to the reactive head group of α-TOH, reacts competitively with added antioxidants for peroxyl radicals -with more effective ones suppressing probe oxidation. 25 Interestingly, both thiosulfinates were completely ineffective at suppressing probe oxidation in unilammelar liposomes, implying that the rates of their reactions with peroxyl radicals in lipid bilayers were at least 100-fold less than α-TOH. We surmised that this was because the sulfenic D r a f t acids derived from both allicin and petivericin could partition to the surrounding aqueous medium -away from lipid-derived peroxyl radicals -where they would undergo other (non-RTA) reactions.…”
Section: Allicin As a Radical-trapping Antioxidant: The Medium Mamentioning
confidence: 99%
“…retarding of the initial rate of fluorescence increase in Figure 2C relative to Figures 2A and 2B), it was still quite poor compared to established RTAs, such as α-TOH. 25,26 However, since sulfenic acid formation from thiosulfinates can also be achieved via reaction with a good nucleophile, such as a thiol, we also investigated whether sulfenic acid formation could be promoted by addition of N-acetylcysteine (NAC) to the buffer in which the liposomes were suspended. While doing so had no effect on the (lack of) activity of allicin and petivericin, a remarkable effect was observed on the hexylated petivericin-inhibited oxidations (cf.…”
Section: Allicin As a Radical-trapping Antioxidant: The Medium Mamentioning
confidence: 99%
“…6 Suitably positioned chalcogens (Se, S) have also been found to increase the radical trapping activity of phenolic compounds. 7 Recently, our group showed that alkyltelluro substituted ß-, γ-and δ-tocopherols 7a-7d…”
mentioning
confidence: 99%